Utility of Metagenomic Next-Generation Sequencing in Infective Endocarditis: A Systematic Review - Sara F. Haddad; Daniel C. DeSimone; Supavit Chesdachai; Danielle J. Gerberi; Larry M. Baddour (MDPI AG, 2022)
Blood cultures have been the gold standard for identifying pathogens in infective endocarditis (IE). Blood culture-negative endocarditis (BCNE), however, occurs in 40% or more of IE cases with the bulk of them due to recent antibiotic exposure prior to obtaining blood cultures. Increasingly, molecular techniques are being used for pathogen identification in cases of BCNE and more recently has included metagenomic next-generation sequencing (mNGS). We therefore performed a literature search on August 31, 2022, that assessed the mNGS in IE and 13 publications were identified and included in a systematic review. Eight (61.5%) of them focused only on IE with mNGS performed on cardiac valve tissue in four studies, plasma in three studies and cardiac implantable electronic devices (CIED) in one study. Gram-positive cocci, including Staphylococcus aureus (n = 31, 8.9%), coagulase-negative staphylococci (n = 61, 17.6%), streptococci (n = 130, 37.5%), and Enterococcus faecalis (n = 23, 6.6%) were the predominant organisms identified by mNGS. Subsequent investigations are needed to further define the utility of mNGS in BCNE and its impact on patient outcomes. Despite some pitfalls, mNGS seems to be of value in pathogen identification in IE cases, particularly in those with BCNE. This study was registered and on the Open Science Framework platform.